Serum and urinary tissue polypeptide antigen (TPA) in patients with urological cancer - Kazama, T (Hinyokika kiyo. Acta urologica Japonica, 1985)
We measured the serum and urinary TPA in 64 patients with urological cancer, 55 patients with benign urological disease and 37 healthy volunteers. The serum TPA levels in patients with pre-treated cancer were significantly higher than those of healthy volunteers, but showed no significant difference compared to those in patients with a benign urological disease. The urinary TPA levels in patients with pre-treated cancer were significantly higher than those with a benign urological disease, but in some patients with urinary tract infection, very high urinary TPA concentrations were observed. Therefore, the determination of serum and urinary TPA may be useful in detecting urological cancer, but they were not specific tests. On the other hand, as lower serum and urinary TPA levels were observed after treatment of bladder and prostatic cancer, their determinations were considered to be useful in following up patients with these cancers